Wild Landscape Perception in the Iliad. The Early Presence of Emotions Associated with Forests and Mountains in Ancient Greek Imagery - García Martín, María Luisa (Gerión. Revista de Historia Antigua, 2022)
How did ancient Greeks experience their relationship with wild Nature? What feelings did a walk in the forest or a night spent in the woods evoke in them? Over the centuries, literature has built bridges between them and us and can bring us a little closer to grasping a hint of their mentality. Our analysis of the passages and similes that mention the natural world in the Iliad could shed some light on how they perceived their natural environment. Mountains and forests aroused different feelings in the minds of ancient Greeks, showing how fear, sacredness, bravery and fascination could converge in their rich and complex perception of the landscape.
Keywords: Nature; wilderness; literature; Homer; Epic; Ancient Greece